A Novel Flavone Glycoside-6,4'-Dihydroxy-3'-Prenyl-3,5,7,5'-Tetramethoxy Flavone-6-O-α-L-rhamnopyranoside from the Seeds of Bauhinia purpurea. - YADAVA, R.N.; SODHI., SHEETAL (Asian Journal of Chemistry, 2010)
Bauhinia purpurea is commonly known as 'Kaniar' in Hindi. It is found in sub-Himalayan tracts up to 4000 ft above sea level. A novel bio-active flavone glycoside. m.f. C30H36O12, m.p. 272- 273°C, M+ 588 [ElMS] was isolated from the acetone souble fraction of ethanolic extract from the seeds of B. purpurea and its structure was established as 6,4'-dihydroxy-3'-prenyl-3, 5, 7, 5'-tetramethoxy flavone-6-O-α-L-rhamnopyranoside by various chemical degradations, chromatographic and spectroscopic methods.